Passiflora rupestris, a new synonym of Passiflora pohlii (Passifloraceae sensu stricto) - Milward-De-Azevedo, Michaele A. (Phytotaxa, 2022)
Passiflora rupestris Bernacci, Mezzonato & Salimena (2014: 517) (Passifloraceae sensu stricto) belongs to the genus Passiflora L. (1753: 955) subgenus Decaloba (DC.) Reichenbach (1828: 132) supersection Decaloba (DC.) J.M. MacDougal & Feuillet (2003 [2004]: 37) section Decaloba DC. (1822: 435). It was described based on a single collection from Serra Negra, Minas Gerais State, Brazil (L. Menini Neto et al. 284 - CESJ 48511). The authors stated in the protologue that the species was closely related to P. condorita P. Jørg. (2004: 18), native to Ecuador, P. magdalenae Triana & Planch. (1873: 166) from Colombia, and a couple of Brazilian species: P. pardifolia Vanderplank (2006: 243) and P. pohlii Mast. (1872: 586). All of those have similarities with respect to leaf shape and the blade lobe apex, but differ in a wider set of features, such as the blades not having ocelli.